Unraveling the “smart but evil” stereotype: pre-service teachers' evaluations of educational psychology researchers versus teachers as sources of information - Hendriks, Friederike; Seifried, Eva; Menz, Cordelia (Zeitschrift für pädagogische Psychologie, 2021)
To guide their professional practice, (pre-service) teachers consider information from a variety of sources. One prerequisite for source preference is the extent to which a source is considered as expert, integer, and benevolent (i.e., its ascribed epistemic trustworthiness). Recent research indicates that pre-service teachers ascribe more expertise but less integrity and benevolence to educational researchers than to practitioners (Merk & Rosman, 2019). However, whether this so-called “smart but evil” stereotype holds true for different epistemic aims is still unknown. In a study with N = 389 pre-service teachers, we analyzed (a) which overarching epistemic aims (i.e., to understand educational research vs. to gather practical knowledge) pre-service teachers have when entering university courses in educational psychology, (b) whether they ascribe higher expertise but lower integrity and benevolence to educational psychology researchers as compared to teachers (i.e., the “smart but evil” stereotype), but also (c) whether these trustworthiness ratings differ for different epistemic aims, and (d) whether pre-service teachers' ascriptions of epistemic trustworthiness to researchers are associated with their perceived usefulness of educational research for teaching practice. We used a within-subject design, asking participants to rate the epistemic trustworthiness of educational psychology researchers versus teachers for two epistemic aims (explanations vs. practical advice). In short, the results only partially support a “smart but evil” interpretation; they show that trustworthiness ratings are in fact adapted to epistemic aims. Hence, our results show that different epistemic aims influence how the trustworthiness of an information source is evaluated.
Gesehen am 25.01.2021